Acute stress-induced changes in hormone and lipid levels in mouse plasma - T. Ahn; C.-S. Bae; C.-H. Yun (Veterinární Medicína, 2016)
We evaluated the conventional acute stress model in mice and investigated the stress-induced changes in concentrations of plasma lipids and hormones such as corticosterone (CORT), insulin, glucagon, triiodothyronine (T3), and thyroxine (T4). Stress induction for 120 min using tape-immobilisation and restraint resulted in an increase in the plasma levels of CORT, insulin, glucose, total cholesterol (TC), and low density lipoprotein-cholesterol compared with unstressed mice. Stress also resulted in a decrease in the concentrations of T3, T4, triglycerides (TG), and high density lipoprotein-cholesterol. However, the amount of glucagon did not change. Moreover, the concentrations of T3, T4, TC, TG, and lipoprotein cholesterol were maintained at constant levels over the recovery periods after stress induction; however, CORT, glucose, and insulin concentrations decreased as a function of time. Statistical correlations between the parameters that changed in response to acute stress were also investigated. In contrast, stress induction for 30 or 60 min did not cause substantial changes in the lipid profiles, although there were fluctuations in the levels of some hormones. This study thus introduces an appropriate model for the study of the acute stress response of lipids and hormones and our data suggest that acute stress affects the levels of plasma lipids, especially cholesterol, in mice.